The Relationship Between Self Management and Academic Stress of Bachelor Students Faculty of Psychology - Shella Monica Santoso; Susana Prapunoto (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This research aims to determine the correlation between self-management and academic stress among undergraduate students of the Faculty of Psychology at Satya Wacana Christian University. Method: The method used in this research is a quantitative method with a correlational design. The population in this study consists of 1238 active undergraduate students of the Faculty of Psychology at Satya Wacana Christian University. Meanwhile, 147 active undergraduate students of the Faculty of Psychology at Satya Wacana Christian University were used as research participants. The sampling technique employed is simple random sampling. Result: The research findings indicate a relationship between self-management and academic stress among undergraduate students of the Faculty of Psychology at SWCU. This suggests that high self-management among students is associated with low academic stress experienced by students of the Faculty of Psychology at SWCU. Conversely, low self-management among students is also associated with high academic stress experienced by students of the Faculty of Psychology at SWCU. Novelty: This research was selected because of its high relevance for psychology scholars. Understanding and maintaining mental health is crucial for them so that in the future, they can effectively assist others and optimize the psychological knowledge acquired during their studies.